Altitudinal variation in life‐history traits in the lawn ground cricket, Polionemobius mikado. Issue 2 (4th April 2019) - Matsuda, Naoki; Numata, Hideharu
Abstract: It has been reported that the lawn ground cricket, Polionemobius mikado (Orthoptera: Trigonidiidae), shows variations in voltinism and life‐history traits along latitude in Japan, but whether it shows variations along altitude has not been examined. The present study aims to determine whether there is variation in voltinism, body size and the incidence of embryonic diapause among populations of P. mikado at different altitudes in Kyoto, Japan. Six populations collected from 70 to 800 m a.s.l. showed a positive relationship between the adult head width and the altitude of sampling locality. This body size cline is attributed to the increasing proportion of larger univoltine individuals from low to high altitude. The incidence of diapause of the strain from altitude 800 m was approximately 100% when reared under natural photoperiods and temperatures from spring to summer at an altitude of 70 m, and was significantly higher than that of the strain from 70 m. These differences in life‐history traits suggest that the population of P. mikado at a higher altitude has adapted to a shorter length of the season available for growth. Abstract : Six populations of Polionemobius mikado collected from various altitudes showed a positive relationship between the adult head width and the altitude, according to the increasing proportion of larger univoltine individuals from low to high altitude. A laboratory strain derived from a high altitude produced mostly diapause eggs, whereas that from a low altitude produced some non‐diapause eggs under natural photoperiods and temperatures at the low altitude. The population at a higher altitude has adapted to a shorter growing season.